Altern Im Wandel 2016
DOI: 10.1007/978-3-658-12502-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Daten und Methoden des Deutschen Alterssurveys

Abstract: KernaussagenDer Deutsche Alterssurvey (DEAS) untersucht die Lebenssitua onen und Alternsverläufe der Menschen in der zweiten Lebenshäl e über einen Zeitraum von bislang 18 Jahren: Zwischen 1996 und 2014 wurden fünf Erhebungen durchgeführt (1996, 2002, 2008, 2011, 2014 EinleitungDer Deutsche Alterssurvey (DEAS) ist eine seit 1996 durchgeführte Befragung von Menschen in der zweiten Lebenshälft e in Deutschland. Mit der jüngsten DEAS-Erhebung im Jahr 2014 hat sich der Beobachtungszeitraum der Studie auf nunmehr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 16 publications
3
32
0
1
Order By: Relevance
“…However, given the assumption that this bias is constant within individuals over time, it did not bias the FE estimates used in our study. Sample selection bias was likely to occur in our study, but it has been argued that this bias was not severe . Panel attrition might have also been a threat, but there is evidence that panel attrition is not a critical problem in the German Ageing Survey .…”
Section: Discussionmentioning
confidence: 78%
“…However, given the assumption that this bias is constant within individuals over time, it did not bias the FE estimates used in our study. Sample selection bias was likely to occur in our study, but it has been argued that this bias was not severe . Panel attrition might have also been a threat, but there is evidence that panel attrition is not a critical problem in the German Ageing Survey .…”
Section: Discussionmentioning
confidence: 78%
“…Future studies, for example based on longitudinal designs, are required to clarify the directionality. Klaus and Engstler ( 44 ) have shown that a small sample selection bias exists in the DEAS study.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of follow‐up data was mainly due to refused participation or for reasons of health. More details were provided elsewhere . It is worth mentioning that the first wave was not used because key variables (e.g.…”
Section: Methodsmentioning
confidence: 99%